Virtual reality as a tool for perceptual evaluation of display characteristics - Visbecq, Nicolas; Moosavi, Mahdiyehsadat; Farrugia, Jean-Philippe; Merienne, Frédéric; Rabellino, Frédéric (Frontiers in Virtual Reality, 2025)
IntroductionThis paper explores the feasibility of using virtual reality (VR) environments to evaluate the technical characteristics of displays. Based on a literature review, we analyze key display parameters, such as resolution, refresh rate, and luminance, as well as human perception and evaluation methods.MethodsAn experimental study was conducted comparing the perception of these parameters in a physical environment and in two virtual reality cases, using high- and low-resolution VR headsets.Results and discussionThe results show that the perception of luminance and refresh rate variations is reliable in VR environments, especially with high-resolution headsets, while the detection of resolution differences remains limited.